Analisis Tingkat Literasi Keuangan Mahasiswa Diploma dan Sarjana serta Perbedaannya Berdasarkan Faktor Demografi - Umma, I’ana; Afrizal, Teuku (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study focuses on analyzing the literacy level of diploma and undergraduate students. Besides understanding the differences based on demographic factors including gender, parental education, parents' income, and education level. The research data was collected through an online survey which was distributed to 500 respondents throughout Indonesia using social media. The data collected was 301 respondents. Then analyzed using the independent sample t test. The results found that the level of financial literacy of diploma and undergraduate students was low. It was also found that there was no difference in the level of student financial literacy based on gender, parental education, parents' income and the level of education that students were taking.